Perpustakaan madrasah sebagai pusat informasi dan sumber belajar bagi siswa - Mohammad Mansyur; Abadi Abadi (IJAL (Indonesian Journal of Academic Librarianship), 2020)
Almost every madrasah is equipped with library facilities as a source of information for students in the morning. The library provides a variety of services and a complete collection that students can use to fulfill their information needs. Also, the development of collections to fulfill information needs can be said to be routinely held for enrichment of reference materials. Whether printed collections such as books, newspapers, magazines, and dictionaries or digital collections such as providing internet access for users in the use of ebooks and e journals, which are available free of charge. With the improvement of excellent service and the realization of cooperation between libraries and external parties, it is hoped that the library will not only function as a center for information sources but also as a learning resource for students. Students can carry out independent learning in the library, such as reading or completing school assignments with the convenient use of services and collections in the library.